Literature Review: Therapy Playing Lego as A method of Anxiety Reduction - Lulu Lutfiyani Solihat (Jurnal Berita Ilmu Keperawatan, 2020)
Introduction: Hospitalized still be an unpleseasant experience and cause traumatic for children. So that children express with a feeling of angst, angry, fear, sad therefore need exerts his therapy playing for minimize anxiety on a child. Objective: The purpose of this literature study to find out therapy playing lego as the lower anxiety at the age of a preschool due to the hospitalized. Method: Research using data such as a base Google Scholar, PubMed, Elseveir, Science Direct and Pro-Ques with the key word in period 2015-2020. Results: Once in the 20 journal in accordance with the title and the results of a matrix by the synthesis in the group into three part of of the input, the process and output. Discussion: After done analysis of 20 journal provision therapy playing on the give positive influence of thw anxiety children are heavy became lighter was. Conclusion: Therapy playing lego effective used us a method of anxiety at the age of a preschool, besides being able to improve the remember and feeling and emotions, lego can also reduce anxiety in children due to the hospitalization.